Rate Integrating Gyroscope Using Independently Controlled CW and CCW Modes on Single Resonator - Tsukamoto, Takashiro; Tanaka, Shuji (Journal of microelectromechanical systems, 2021)
This paper reports a rate integrating gyroscope (RIG) using independently controlled clockwise (CW) and counter clockwise (CCW) modes on a single MEMS resonator. The rotation angle is read out by the phase difference between these modes. A CW/CCW mode separator was used to independently contol these modes superposed on the resonator. The frequency and Q-factor mismatches were compensated by the phases and amplitudes of driving signals. A control system including the mode separator, feedback controllers, signal generators, mismatch compensators were implemented in a field programmable gate array (FPGA). Using the proposed mismatch compensation technique, the equivallent aniso-damping term became 1/100. As a result, the scale factor became constant and the non-linearity became less than 0.2% even when the slow angular rate region around 5°/s. In addition, the temperature coefficient of scale factor as small as −1.84 ± 0.62 ppm/K was achieved without any temperature correction. [2020-0011]